THE REPRESENTATION INDIGENOUS GUARANI MEMOIR IN BOOKS - Caroline Hermínio Maldonado; Antônio Jacó Brand (Espaço Ameríndio, 2010)
The works of authors memoir, researched this, depict the lifestyles Guarani and conflicts involving territorial disputes between the eighteenth and mid-twentieth century. They report experiences and seek their opinion about the relationship between indigenous people and migrants, as the authors themselves, who came to southern Ontario then on business and looking for productive land. From these works it is understood as the Indians managed to hide the regional history and justify their judgments about this population without considering the culture and without social organization. The research is to understand the phenomenon of invisibility to which they are subject, not only the Guarani, but the other indigenous peoples today the state of Mato Grosso do Sul.